2016
DOI: 10.1111/jpi.12358
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin‐induced increase in sensitivity of human hepatocellular carcinoma cells to sorafenib is associated with reactive oxygen species production and mitophagy

Abstract: Effects of sorafenib in hepatocellular carcinoma (HCC) are frequently transient due to tumor-acquired resistance, a phenotype that could be targeted by other molecules to reduce this adaptive response. Because melatonin is known to exert antitumor effects in HCC cells, this study investigated whether and how melatonin reduces resistance to sorafenib. Susceptibility to sorafenib (10 nM to 50 μM) in the presence of melatonin (1 and 2 mM) was assessed in HCC cell lines HepG2, HuH7 and Hep3B. Cell viability was re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
144
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(150 citation statements)
references
References 70 publications
(151 reference statements)
6
144
0
Order By: Relevance
“…The present study confirms that the activated JNK/c‐jun pathway is responsible for the activation of caspase‐3. It is also demonstrated that the combination of melatonin and sorafenib induces increased apoptosis and reduced viability through ROS overproduction and mitochondrial membrane depolarization . Furthermore, ROS/JNK/c‐Jun signaling pathway was reported to be involved in regulating the apoptosis of HCC cells .…”
Section: Discussionmentioning
confidence: 98%
“…The present study confirms that the activated JNK/c‐jun pathway is responsible for the activation of caspase‐3. It is also demonstrated that the combination of melatonin and sorafenib induces increased apoptosis and reduced viability through ROS overproduction and mitochondrial membrane depolarization . Furthermore, ROS/JNK/c‐Jun signaling pathway was reported to be involved in regulating the apoptosis of HCC cells .…”
Section: Discussionmentioning
confidence: 98%
“…Likewise, the mitophagy level is decreased in M1 macrophages in vivo . Indeed, melatonin has been reported to elevate the mitophagy level in other systems . However, the exact mechanisms whereby melatonin targets mitophagy remain to be identified.…”
Section: Mechanisms Whereby Melatonin Regulates Macrophage Polarizationmentioning
confidence: 99%
“…This speculation is supported by the observations summarized herein that melatonin indeed targets the process of mitophagy. Melatonin mainly enhances mitophagy and improves mitochondrial biogenesis [203,204,205]. The exact mechanisms by which melatonin targets mitophagy are not currently available.…”
Section: Melatonin Regulates Mitochondrial Dynamicsmentioning
confidence: 99%